Question
upstudy study bank question image url

et X have the probability distribution \( \mathrm{f}(\mathrm{x})=\frac{1}{4} \times\binom{ 2}{\mathrm{x}} \quad \mathrm{x}=0,1,2 \) Obtain (i) \( M_{x}^{\prime}(t) \) (ii) \( M_{x}^{\prime \prime}(t) \) (iii) \( \operatorname{Var}(\mathrm{x}) \)

Ask by Lambert Fowler. in Nigeria
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(i) \( M'_X(t) = \frac{1}{2}(e^t + e^{2t}) \) (ii) \( M''_X(t) = \frac{1}{2}(e^t + 2e^{2t}) \) (iii) \( \operatorname{Var}(X) = \frac{1}{2} \)

Solution

We are given that the probability mass function of X is   f(x) = (1/4) × (2 choose x),  for x = 0, 1, 2. Notice that   (2 choose 0) = 1, (2 choose 1) = 2, (2 choose 2) = 1, so the probabilities are   P(X = 0) = 1/4,   P(X = 1) = 2/4 = 1/2,   P(X = 2) = 1/4. This is the binomial distribution with n = 2 and p = 1/2. Step 1. Moment Generating Function (MGF): The moment generating function (MGF) is defined by   M_X(t) = E(e^(tX)) = Σ (e^(tx) f(x)). Thus,   M_X(t) = (1/4)[e^(0t) (2 choose 0) + e^(t) (2 choose 1) + e^(2t) (2 choose 2)]        = (1/4)[1 + 2e^t + e^(2t)]. Step 2. (i) First Derivative M'_X(t): Differentiate M_X(t) with respect to t:   M_X(t) = (1/4)[1 + 2e^t + e^(2t)]. Differentiate term by term:   d/dt (1) = 0,   d/dt (2e^t) = 2e^t,   d/dt (e^(2t)) = 2e^(2t). Thus,   M'_X(t) = (1/4)[0 + 2e^t + 2e^(2t)] = (1/4) × 2 [e^t + e^(2t)]         = (1/2)[e^t + e^(2t)]. Step 3. (ii) Second Derivative M''_X(t): Differentiate M'_X(t) with respect to t:   M'_X(t) = (1/2)[e^t + e^(2t)]. Differentiate term by term:   d/dt (e^t) = e^t,   d/dt (e^(2t)) = 2e^(2t). Thus,   M''_X(t) = (1/2)[e^t + 2e^(2t)]. Step 4. (iii) Variance Var(X): Recall that   Var(X) = E(X²) – [E(X)]², and we can obtain E(X) = M'_X(0) and E(X²) = M''_X(0). • First, compute E(X):   M'_X(t) = (1/2)[e^t + e^(2t)], so M'_X(0) = (1/2)[e^0 + e^0] = (1/2)[1 + 1] = 1.   Thus, E(X) = 1. • Next, compute E(X²):   M''_X(t) = (1/2)[e^t + 2e^(2t)], so M''_X(0) = (1/2)[1 + 2×1] = (1/2)[3] = 3/2.   Thus, E(X²) = 3/2. • Therefore, the variance is   Var(X) = E(X²) – [E(X)]² = (3/2) – (1)² = (3/2) – 1 = 1/2. Final Answers: (i) M'_X(t) = (1/2)[e^t + e^(2t)] (ii) M''_X(t) = (1/2)[e^t + 2e^(2t)] (iii) Var(X) = 1/2.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve for the moment generating function and variance from the given probability distribution \( \mathrm{f}(\mathrm{x})=\frac{1}{4} \times\binom{ 2}{\mathrm{x}} \) for \( \mathrm{x}=0,1,2 \), we start by calculating the moment generating function \( M_x(t) \). ### Step 1: Find \( M_x(t) \) The moment generating function is defined as: \[ M_x(t) = E[e^{tX}] = \sum_{x=0}^{2} e^{tx} f(x) \] Substituting in the values: \[ M_x(t) = \sum_{x=0}^{2} e^{tx} \left( \frac{1}{4} \binom{2}{x} \right) \] Calculating each term: - For \( x=0 \): \( e^{t \cdot 0} \cdot \frac{1}{4} \cdot \binom{2}{0} = 1 \cdot \frac{1}{4} \cdot 1 = \frac{1}{4} \) - For \( x=1 \): \( e^{t \cdot 1} \cdot \frac{1}{4} \cdot \binom{2}{1} = e^t \cdot \frac{1}{4} \cdot 2 = \frac{1}{2} e^t \) - For \( x=2 \): \( e^{t \cdot 2} \cdot \frac{1}{4} \cdot \binom{2}{2} = e^{2t} \cdot \frac{1}{4} \cdot 1 = \frac{1}{4} e^{2t} \) Adding these up gives: \[ M_x(t) = \frac{1}{4} + \frac{1}{2} e^t + \frac{1}{4} e^{2t} \] ### Step 2: Find \( M_x^{\prime}(t) \) Now we differentiate \( M_x(t) \): \[ M_x^{\prime}(t) = \frac{d}{dt}\left( \frac{1}{4} + \frac{1}{2} e^t + \frac{1}{4} e^{2t} \right) \] \[ = 0 + \frac{1}{2} e^t + \frac{1}{4} \cdot 2 e^{2t} = \frac{1}{2} e^t + \frac{1}{2} e^{2t} = \frac{1}{2}(e^t + e^{2t}) \] ### Step 3: Find \( M_x^{\prime \prime}(t) \) Now we differentiate \( M_x^{\prime}(t) \): \[ M_x^{\prime \prime}(t) = \frac{d}{dt}\left( \frac{1}{2}(e^t + e^{2t}) \right) \] \[ = \frac{1}{2}(e^t + 2 e^{2t}) = \frac{1}{2} e^t + e^{2t} \] ### Step 4: Find \( \operatorname{Var}(X) \) The variance can be computed using: \[ \operatorname{Var}(X) = M_x^{\prime \prime}(0) - (M_x^{\prime}(0))^2 \] First, we calculate \( M_x^{\prime}(0) \) and \( M_x^{\prime \prime}(0) \): \[ M_x^{\prime}(0) = \frac{1}{2}(e^0 + e^{0}) = \frac{1}{2}(1 + 1) = 1 \] \[ M_x^{\prime \prime}(0) = \frac{1}{2} e^0 + e^{0} = \frac{1}{2} \cdot 1 + 1 = \frac{3}{2} \] Thus, we find the variance: \[ \operatorname{Var}(X) = M_x^{\prime \prime}(0) - (M_x^{\prime}(0))^2 = \frac{3}{2} - 1^2 = \frac{3}{2} - 1 = \frac{1}{2} \] ### Summary of Results - \( M_x^{\prime}(t) = \frac

Related Questions

Latest Probability Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy